Case report: Parsonage-turner syndrome in a melanoma patient treated by BRAF/MEK inhibitors after immune checkpoint inhibitors - Bonnefin, Charlotte; Duval, Fanny; Rouanet, Marie; Kostine, Marie; Gerard, Emilie (Frontiers in Oncology, 2023)
Introduction: Combination molecular BRAF/MEK inhibitors targeted therapy has been shown to improve overall survival in patients with BRAF V600 mutated unresectable or metastatic melanoma. Most patients treated with BRAF/MEK inhibitors will experience adverse events but neurological adverse events (nAEs) remain rare.Case report : A 42-year-old woman diagnosed with metastatic melanoma presented with an intense pain in the left shoulder 7 days after the beginning of encorafenib/binimetinib after immune checkpoint inhibitors (ICI) combination. No other triggering factors were identified. Electromyogram performed one month after the pain onset revealed a left brachial plexopathy suggestive of a Parsonage-Turner syndrome. The weakness slowly improved with intensive rehabilitation and targeted therapies were continued.We report the first case of Parsonage-Turner syndrome in a melanoma patient treated with encorafenib /binimetinib following checkpoint inhibitors combination.We cannot rule out the implication of ICI in the development of this syndrome but the rapid onset of the symptoms after the beginning of targeted therapies makes their involvment more likely.Given the increased use of BRAF/MEK inhibitors in managing of stage III and IV melanoma, as well as the development in stage II, clinicians should be aware of this potential side effect.